2021
DOI: 10.2478/rjim-2020-0028
|View full text |Cite
|
Sign up to set email alerts
|

Is improvement of fatigue in rheumatoid arthritis a proper effect of biologics?

Abstract: Background: The objective of our present study is to assess the relation between persistent fatigue and rheumatoid arthritis (RA) disease activity and its functional impact and to determine if the positive effect of biologics on fatigue is due to good disease response or to a different pathway.Methods: A study cohort of patients with established RA was conducted. We included patients who were initiation a biologic after at least failure of one conventional synthetic Disease Modifying Anti-Rheumatic Drug synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The main findings of our study were as follows: Although the exact mechanism is still unclear, evidence shows that disease-related factors (inflammation, pain, and so on), medication administration, cognitive and behavioral factors, and personal factors (personal responsibilities, personal environments, social support, personal health, and dietary patterns) can contribute to fatigue in RA patients. 4,[25][26][27] As a common chronic symptom in RA patients, fatigue brings great burdens to patients, including daily activity obstacles, decreased work ability, economic loss, and so on. 28,29 Previous studies show the prevalence of fatigue in RA is about 44.00%-71.25% and the fatigue score in RA patients is higher than in healthy controls, indicating that fatigue is widespread among RA patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main findings of our study were as follows: Although the exact mechanism is still unclear, evidence shows that disease-related factors (inflammation, pain, and so on), medication administration, cognitive and behavioral factors, and personal factors (personal responsibilities, personal environments, social support, personal health, and dietary patterns) can contribute to fatigue in RA patients. 4,[25][26][27] As a common chronic symptom in RA patients, fatigue brings great burdens to patients, including daily activity obstacles, decreased work ability, economic loss, and so on. 28,29 Previous studies show the prevalence of fatigue in RA is about 44.00%-71.25% and the fatigue score in RA patients is higher than in healthy controls, indicating that fatigue is widespread among RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanism is still unclear, evidence shows that disease‐related factors (inflammation, pain, and so on), medication administration, cognitive and behavioral factors, and personal factors (personal responsibilities, personal environments, social support, personal health, and dietary patterns) can contribute to fatigue in RA patients 4,25–27 . As a common chronic symptom in RA patients, fatigue brings great burdens to patients, including daily activity obstacles, decreased work ability, economic loss, and so on 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Our studies did not show any relationship between pharmacological therapy and an increase in fatigue. Ines et al [ 32 ] conducted a cohort study where they assessed, among other things, the effect of biological treatment (anti-TNFα) on fatigue symptoms, and a significant decrease in the level of fatigue was noted. Janoudi et al [ 33 ] confirmed that several months’ use of adalimumab reduces the symptoms of fatigue as measured by the FACIT-F scale.…”
Section: Discussionmentioning
confidence: 99%